Trans IL-6 signaling does not appear to play a role in renal scarring after urinary tract infection. Issue 5 (October 2020) - Gupta, Sudipti; Junquera, Guillermo Yepes; Nicassio, Lauren; Becknell, Brian; Ching, Christina B.
Summary: Introduction: While inflammation is an important innate defense mechanism against infection, it can also lead to local tissue damage. The trans signaling pathway of interleukin (IL)-6 is a known mediator of inflammation. We hypothesized that the trans IL-6 signaling pathway is associated with the development of post febrile urinary tract infection (UTI) renal scarring. Objective: To compare soluble regulators of trans IL-6 signaling between patients with a history of febrile UTI who do or do not have renal scarring. Study design: After IRB-approval, we collected urine samples in pediatric patients with a history of febrile (≥38 °C) UTI (urine culture >50 K uropathogen) with documented presence or absence of renal scarring on imaging. Samples were collected at a time when patients were not actively infected. Enzyme-linked immunosorbent assays were performed on samples for markers of trans IL-6 signaling: IL-6, soluble (s) IL-6 receptor (R), and soluble (s)gp130, a buffer in trans IL-6 signaling. Values were normalized to urine creatinine. Results were analyzed by t -test or Mann–Whitney U. Spearman rank correlation was used. A p-value of <0.05 was considered significant. Results: A total of 50 urines from patients with a history of febrile UTI were collected: 23 with and 27 without scarring. There was no difference between groups regarding age or gender. There was no significant difference in urine IL-6, sIL-6R, or sgp130 between those with and without scarring (Figure). While IL-6 values significantly correlated with sIL-6R and sgp130 in those without renal scarring, IL-6 did not correlate with sgp130 in those with scarring. Ratios of IL-6 to sgp130 and sIL-6R to sgp130 were not different between groups. Discussion: The inflammatory response generated in response to infection is believed to be largely responsible for the development of renal scarring after UTI. IL-6 is a cytokine known to be induced during UTI with a pro-inflammatory pathway, known as trans signaling. This study investigated for differences in markers of trans IL-6 signaling between patients with a history of febrile UTI with and without renal scarring. There was no significant difference between the absolute values or ratio of these markers between groups. Conclusions: Markers of trans IL-6 signaling are not different between individuals with a history of febrile UTI with and without renal scarring in the non-acute setting. Summary Fig. 1 Urine sample results of trans IL-6 signaling markers in patients with a history of febrile UTI who do not have scarring (NS) compared to those with scarring (S). Summary Fig. 1